A Rare Footprint: A Case Report of Isolated Pre-Axial Fully Developed Supernumerary Toe - Varun Kumar; Mohan Choudhary; Srinivasan Rajappa; Kevin Lourdes; Arjun Ganesh; P Velmurugan (Journal of Orthopaedic Case Reports)
Introduction: Polydactyly of the foot, particularly pre-axial polydactyly, is a rare congenital malformation that can occur alongside various congenital anomalies and syndromes. Classification of polydactyly, such as Venn-Watson’s system, aids in understanding the complexity and variability of this congenital condition. Case Report: This case report details the presentation and surgical intervention of a 5-year-old boy with pre-axial polydactyly characterized by an accessory toe on the right foot, which had hindered his ability to walk properly since birth and his journey through surgical excision for a better stand in life. Conclusion: Pre-axial polydactyly of the foot is a rare congenital anomaly that can significantly affect mobility and quality of life. Early diagnosis, aided by a detailed clinical evaluation and radiographic imaging, is crucial for appropriate management.